Evaluasi Kompetensi Vendor terhadap Efektivitas Pengadaan Jasa di PT. PYX - Rangga Saputra; Sulastri Irbayuni (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity aims to assist PT PYX Supply Chain Division in improving the effectiveness of service procurement through the implementation of a competency-based vendor evaluation system. The main problem faced by partners is that the evaluation process still focuses on administrative and legal aspects of documents, so it is not yet able to fully describe the technical and managerial capabilities of vendors. The activity was carried out in the form of mentoring and technical assistance to procurement staff through several stages, including analysis of the evaluation system requirements, preparation of competency-based assessment formats, training in the use of evaluation instruments, and trial implementation in the partner's work environment. The results of the activity showed an increase in staff understanding and ability to assess vendor competencies objectively and measurably. The application of the new evaluation instruments also had a positive impact on the timeliness of the procurement process and increased consistency in assessment results between vendors. This activity made a real contribution to the company in developing a more professional, efficient, and competency-based procurement system.